Credit when you need it - Benjamin L. Collier; Daniel A. Hartley; Benjamin J. Keys; Jing Xian Ng (Federal Reserve Bank of Chicago, 2024)
We estimate the causal effect of emergency credit on households' finances after a negative shock. To do so, we link application data from the U.S. Federal Disaster Loan program, which provides loans to households that have uninsured damages from a federally-declared natural disaster, to a panel of credit records before and after the shock. We exploit a discontinuity in the loan approval rules that led applicants with debt-to-income ratios below 40% to be differentially likely to be approved. Using an instrumented difference-in-differences research design, we find that credit provision at the time of a shock significantly reduces severe financial distress, decreasing the likelihood of filing for bankruptcy by 61% in the three years following the disaster. We explore mechanisms using additional quasi-experimental variation in interest rates, finding support for a liquidity-based explanation. Credit provision in a time of crisis has real consumption effects in the form of additional car purchases even 3 years after loan receipt. Our findings suggest that well-timed liquidity provided to households in acute need can have substantial and persistent positive effects.
Keywords: D14; G23; G28; H81; 330; Consumer credit; disaster loan; personal bankruptcy; delinquency; auto loans; climate risk